2019
DOI: 10.3838/jjo.68.237
|View full text |Cite
|
Sign up to set email alerts
|

The history of anthropogenic disturbance and invasive alien species impact on the indigenous avifauna of the Ogasawara Islands, southern Japan

Abstract: The Ogasawara Islands are subtropical oceanic islands in the Northwestern Pacific. Since their unique ecosystem is recognized to have outstanding universal value, they are registered as a UNESCO World Natural Heritage site. However, human settlement since 1830 has seriously impacted the biota. So far, the breeding of 20 land birds and 21 seabirds, including three introduced species, has been recorded on the islands. Seven endemic species/subspecies have become extinct, and breeding populations of five species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 56 publications
(4 reference statements)
1
20
0
Order By: Relevance
“…The Ogasawara Islands originated as a result of volcanic activity approximately 48 MYA and appeared above sea level during the Eocene epoch (Umino et al, 2016). Therefore, it is difficult to know when these islands were colonized by different bird species, with the exception of those species that have only appeared there for a few decades, such as the common moorhen Gallinula chloropus, the bull-headed shrike Lanius bucephalus, and the scaly thrush Zoothera dauma (Kawakami, 2019). Nakamura (2002) suggested that the Ogasawara Oriental greenfinch population originated as the result of an accidental invasion from a northern population located in Kamchatka, the Kuril Islands, or Hokkaido.…”
Section: Origin Of the Ogasawara Bird Populationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Ogasawara Islands originated as a result of volcanic activity approximately 48 MYA and appeared above sea level during the Eocene epoch (Umino et al, 2016). Therefore, it is difficult to know when these islands were colonized by different bird species, with the exception of those species that have only appeared there for a few decades, such as the common moorhen Gallinula chloropus, the bull-headed shrike Lanius bucephalus, and the scaly thrush Zoothera dauma (Kawakami, 2019). Nakamura (2002) suggested that the Ogasawara Oriental greenfinch population originated as the result of an accidental invasion from a northern population located in Kamchatka, the Kuril Islands, or Hokkaido.…”
Section: Origin Of the Ogasawara Bird Populationsmentioning
confidence: 99%
“…The black rat Rattus rattus, is not found within the breeding range of the Ogasawara greenfinch. This is fortunate, because populations of finches would be unable to survive on islands inhabited by the black rat (Kawakami, 2019). Predation by the black rat is probably the major factor in the local extinction of finch populations.…”
Section: Conservation Of the Ogasawara Greenfinchmentioning
confidence: 99%
See 2 more Smart Citations
“…On the Ogasawara Islands and Teuri Island, adoption programs have effectively reduced the number of feral cats with the estimated population now under 10 on Chichi-Jima Island, which is one of the Ogasawara Islands (Tokyo Veterinary Medical Association, 2016), and the number has been reduced from 143 to closely zero on Teuri Island (Haboro City, 2019). As a result, the populations of endemic species, such as seabirds, have recovered on these islands (Kawakami, 2019).…”
Section: Introductionmentioning
confidence: 99%